EDITORIAL - Prof. Ar Dr. Abdul Razak Sapian (Journal of Architecture, Planning and Construction Management, 2025)
Dear All, Assalamu’alaikum warahmatullahi wabarakatuh. Journal of Architecture, Planning and Construction Management (JAPCM), Kulliyyah of Architecture and Environmental Design is one the official journals of International Islamic University Malaysia (IIUM), under IIUM Press. It embarked in 2011 and is dedicated to the publication of original articles on the specialized fields of Architecture, Planning, Landscape Architecture, Quantity Surveying, Building Technology and Engineering, Applied Arts and Design, Construction Management and those related to the Built Environment. JAPCM is also the ardent forum for the reports of research that bridged the Built Environment and the Islamic worldview. Prof. Ar. Dr. Abdul Razak Sapian Editor-in-Chief